DURATION TIME AND EGGS DENSITY TO IMPROVE CLOSED TRANSPORTATION TECHNOLOGY ON EGGS GROUPER (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
The grouper hatchery technology  has been successfully developed and grouper seed can be produced massively and sustainly. Egg is one of key successes in the hatchery processes. Eggs taken from hatchery egg producer were often far away from a final hatchery location. This study tried to find out the effectiveness of eggs transportation  duration and densities for eggs’ hatchability of tiger grouper (Epinephelus fuscoguttatus). The first treatment: eggs at a density of 400 000 eggs/8 l sea water,  transported with different duration time i.e., 6,  12, 18, and 24 hours. The second treatment: transportation eggs with duration 24-hour  at different density i.e., 100,000; 200,000;300,00; and 400,000 eggs/8 l sea waters.  Eggs were packaged  in a plastic bag with 8 liters of water media, the plastic size 100 cm x 55 cm, ratio water with oxygen was 1: 3, the  plastic bag inserted to sterofoam with size 75 cm x 40 cm x 30 cm, to reduce the temperature in sterofoam was added ice the size of 500 grams , wrapped in newspaper,  styrofoam  covered by selotipe. The results showed that eggs with transportation time  of 6 and 12 hours were better and significantly different (P